The Effectiveness of Cognitive Muscle Therapy for Improving Lumbar Function in Low Back Pain - Astrid Komala Dewi; Catherine Hermawan Salim; Ratu Chairunisa; Elyin Artha Karlina Lumban Gaol (Sean Institute, 2025)
Objective: This study aims to determine the effect of cognitive muscle therapy on improving lumbar function in low back pain. The sample consisted of 40 people and was selected based on random sampling techniques using the available questionnaire. The sample was grouped into two treatment groups, treatment group I consisted of 20 people with Cognitive Muscle Therapy and treatment group II consisted of 20 people with Cognitive Muscle Therapy. Method: This study is a type of quasi-experimental pre-post test design. Statistical analysis of this study used the Related T-Test test and the Independent T-Test test. The results of the homogeneity test of the treatment group before exercise with a p value = 0.008. The results of the Related T-Test test in treatment group I with a p value = 0.001 and in treatment group II with a p value = 0.001 means that the exercise given to each group has an effect on improving Lumbar Function. And the results of the Independent T-Test showed a p value = 0.001 which means there is a very significant effect between treatment group I and treatment group II. It can be concluded that there is a very significant effect of Cognitive Muscle Therapy for Improving Lumbar Function in Low Back Pain. In this study, it is recommended that the exercise method can be applied with the correct procedure, carried out for more than 1 month because the improvement of Lumbar Function will be better if done for 2-3 months, and it is hoped that things that can affect the results of the study can be minimized in order to achieve optimal results.